The Influence of Intellectual Intelligence on the Learning Outcomes of Prospective Physics Teachers - Lestari, Ayu; Revalina, Jihan Alya; Setiaji, Bayu (Jurnal Pendidikan Indonesia, 2023)
IQ is an intelligence related to awareness of space, awareness of what is visible and mastery of mathematics. This research aims to (1) describe the intellectual intelligence of prospective physics education teachers for classes A and C. (2) describe the physics learning outcomes and describe the physics learning outcomes of prospective physics education teachers, and (3) determine the relationship between intellectual intelligence and physics learning outcomes . By knowing the level of readiness of prospective physics education teacher students. The method used is a survey with the type of research being quasi-experimental. Student readiness for prospective physics education teachers is measured using a student readiness questionnaire. This questionnaire has 10 statements with 4 choices. This research involved physics education class A and physics education class C.